2018
DOI: 10.1289/isesisee.2018.p03.0050
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, Risk Perception, and Protective Behaviors for Extreme Heat and Climate Change in New York City

Abstract: Preventing heat-related illness and death requires an understanding of who is at risk and why, and options for intervention. We sought to understand the drivers of socioeconomic disparities in heat-related vulnerability in New York City (NYC), the perceived risk of heat exposure and climate change, and barriers to protective behaviors. A random digit dial telephone survey of 801 NYC adults aged 18 and older was conducted from 22 September-1 October, 2015. Thirteen percent of the population did not possess an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Moreover, whilst research has shown that low-income households may be more concerned about health risks from heat and climate change, low-income households in the US were less likely to have air conditioning at home ( Madrigano et al, 2018 ). Lack of transportation or lack of awareness can prevent the most vulnerable people from accessing and using public cooling centres ( Nayak et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, whilst research has shown that low-income households may be more concerned about health risks from heat and climate change, low-income households in the US were less likely to have air conditioning at home ( Madrigano et al, 2018 ). Lack of transportation or lack of awareness can prevent the most vulnerable people from accessing and using public cooling centres ( Nayak et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%